Affecting Factors Of Customer Interest in Using Mobile Banking at BNI 46 Musi Branch Palembang - Afrizawati; Lidia Desiana; Paisal; Maulidiyah Magfirah (Department of Business Administration Politeknik Negeri Sriwijaya, 2022)
This research was conducted based on customers' interest in mobile banking which continues to increase, especially during Covid 19 pandemic. The purpose of this research is to find out how each variable of convenience, benefit, and risk either partially or simultaneously affects customers’ interest in using mobile banking. The sample in this research was customers of Bank BNI 46 Musi Palembang. There were 100 people who participated in this research. The research method used multiple linear regression. The data quality test used Validity and Reliability tests. The hypothesis was analyzed using t-test, f-test, and determinant (R2). The results indicated that the variables of convenience, benefits, and risks either partially or simultaneously affect customer interest in using mobile banking. Based on the validity tested obtained the value of Significant (2-tailed) 0.000 is smaller than 0.05, which means it is valid, and r count (person correlation) is greater than r table (0.1966) so that the items or questions were valid. While based on reliability, Cronbach’s Alpha > 0.60 means that the data was reliable. The coefficient of Determination (R2) obtained 0.719 which means that 71.9% of customers’ interest was influenced by convenience, benefits, and risk variables, while the remaining 28.1% was influenced by other variables. And the R-value (correlation coefficient) of 0.848 means that there was a strong relationship between variables.